Proteomic and Single-Cell Transcriptomic Dissection of Human Plasmacytoid Dendritic Cell Response to Influenza Virus - Ghanem, Mustafa H.; Shih, Andrew J.; Khalili, Houman; Werth, Emily G.; Chakrabarty, Jayanta K.; Brown, Lewis M.; Simpfendorfer, Kim R.; Gregersen, Peter K. (Frontiers in Immunology, 2022)
Plasmacytoid dendritic cells [pDCs] represent a rare innate immune subset uniquely endowed with the capacity to produce substantial amounts of type-I interferons. This function of pDCs is critical for effective antiviral defenses and has been implicated in autoimmunity. While IFN-I and select cytokines have been recognized as pDC secreted products, a comprehensive agnostic profiling of the pDC secretome in response to a physiologic stimulus has not been reported. We applied LC-MS/MS to catalogue the repertoire of proteins secreted by pDCs in the unperturbed condition and in response to challenge with influenza H1N1. We report the identification of a baseline pDC secretome, and the repertoire of virus-induced proteins including most type-I interferons, various cytokines, chemokines and granzyme B. Additionally, using single-cell RNA-seq [scRNA-seq], we perform multidimensional analyses of pDC transcriptional diversity immediately ex vivo and following stimulation. Our data evidence preexisting pDC heterogeneity, with subsequent highly specialized roles within the pDC population upon stimulation ranging from dedicated cytokine super-producers to cells with APC-like traits. Dynamic expression of transcription factors and surface markers characterize subclusters within activated pDCs. Integrating the proteomic and transcriptomic datasets confirms the pDC-subcluster origin of the proteins identified in the secretome. Our findings represent the most comprehensive molecular characterization of primary human pDCs at baseline, and in response to influenza virus, reported to date.